Pengaruh Brand Image Dan Perceived Value Terhadap Keputusan Menggunakan Aplikasi Bukalapak Dengan Dimediasi Oleh Trust Di Kota Palembang - Putri, Yuni Adinda (Akuntansi dan Manajemen, 2025)
The purpose of this study is to examine the impact of brand image and perceived value on the intention to use the Bukalapak e-commerce platform, with trust serving as a mediating variable, specifically in Palembang. Data was gathered via a poll of 200 participants who are active users of Bukalapak. The findings indicate that brand image and perceived value significantly influence intention to use, both directly and indirectly via trust. The direct influence of brand image on intention to use is 0.40, whereas the direct influence of perceived value is 0.35. Furthermore, trust functions as a mediator that enhances the impact of both variables on intention to use, exhibiting indirect effects of 0.26 for brand image and 0.21 for perceived value. An R² score of 0.70 signifies that the model accounts for 70% of the variability in intention to use. This research advances consumer behaviour theory in e-commerce and offers strategic advice for organisations to improve competitiveness and client loyalty